Reviews - Simon, Shirley (Groupwork, 2017)
Reviews of: Group Activities for Latino/a Youth Strengthening identities and resiliencies through counseling, Edited by Krista M. Malott and Tina R. Paone Inclusive Group Work, by William Pelech, Robert Basso, Cheryl D. Lee, and Maria Gandarilla